(untitled) ([Hong Kong], 1989)
Contents: Part 1: Resources exploitation and utilization; part 2: environmental constraints and management; part 3: regional and Urban development.
Keywords: Natural resources,Environmental policy,Nguồn tài nguyên thiên nhiên,Chính sách môi trường; China,China,Trung Quốc